TELAAH PERKEMBANGAN KONSEP BIOLOGI DALAM PENDIDIKAN DI INDONESIA 1945-1994 : Studi Tentang Konsep Biologi dalam Buku Ajar Pendidikan Dasar dan Menengah - Sri Redjeki, - (1997)
How the concepts of Biology developed in Indonesian education during 1945-1994 was investigated through historical research and scholarly study. The data, in the form of concepts, were collected from 345 books of primary school, junior high school, and senior high school, published in Java and Sumatera, and were used during 1945-1996.The analysis was carried out by comparing the concepts to the curricula and to the data of science and technology at that time. It was found that 1) the contents of the text-books only provide knowledge for entering higher education; 2) the development of science and technology put in the text-books was behind by approximately 50 years; 3) the involvement of the environment could be found more in books which were translated from books during the colonial time; 4) the scope and the sequence of the contents in the text-books, were quite often different from what was required by the curricula. It was found that there were four groups of writers who were not in line with the curricula; 5) the development of the concepts of systematics, structure, physiology, ecology, and genetics included the development of and the way to present the concepts; 6) the development of the concepts in primary school was much more in the field of morphology, diversity, and interaction among organisms; in junior high school the emphasis was on the diversity, the life processes, and the interaction among organisms; while in senior high